PEMBERHENTIAN PENGECORAN BETON UNTUK PEKERJAAN KONSTRUKSI LENTUR BERDASARKAN SNI 2847-2019 - Pratikto, Pratikto; Susilowati, Anni; Gym Wijaya, Abdira (Construction and Material Journal, 2024)
The presence of construction joints is an inevitable aspect of field concrete casting. These joints occur when fresh concrete is poured over hardened concrete, which can impact the strength and integrity of the concrete structure. This study aims to evaluate the placement of concrete joints according to SNI 2847-2019, which recommends placing them at one-third of the span of the beam. Testing was conducted on unreinforced concrete beams with two different joint locations. The concrete used had a water-cement ratio (w/c) of 0.5 and a maximum aggregate size of 25 mm, with the mix design following SNI 7656-2012. The test results indicate that joints placed at one-third of the span exhibit better flexural strength compared to those located at the span's ends. The average flexural strengths of beams without joints, those with joints at one-third of the span, and those with joints at one-third of the end span are 1.95 MPa, 1.56 MPa, and 0.98 MPa, respectively. These findings support the SNI 2847-2019 recommendation for placing concrete joints at one-third of the span of the beam.